Analysis of Environmental, Social, and Governance (ESG) Risks in the Oil and Gas Industry - Deswita Deswita; Iwan Vanany (Journal Research of Social Science, Economics, and Management, 2026)
The oil and gas industry is characterized by high operational risks that significantly affect Environmental, Social, and Governance (ESG) aspects. This study aimed to identify ESG risk events and risk agents, determine the priority levels of risk agents, and formulate effective and efficient mitigation strategies in the oil and gas industry, with PT X as the research object. This research employed a mixed-methods approach. Qualitative risk identification was conducted through document reviews and expert interviews, followed by quantitative assessment using the Analytical Hierarchy Process (AHP) and House of Risk (HOR) Phases 1 and 2 involving 11 expert respondents consisting of professionals, academics, and regulators. The results identified 15 risk events and 15 ESG risk agents. The AHP weighting results showed that the priority order of ESG dimensions was Environmental (40.11%), Social (30.18%), and Governance (29.72%), with an acceptable consistency ratio (CR = 0.0667). Based on the weighted Aggregate Risk Potential (ARP) values and the 80% Pareto principle, 11 priority risk agents were identified, with the highest priority being non-compliance with Bahan Berbahaya dan Beracun (B3) waste management procedures by contractors and subcontractors (ARP = 585.24). The Phase 2 HOR analysis based on the Effectiveness-to-Difficulty (ETD) ratio recommended five priority preventive actions: strengthening workplace safety culture, digitizing the B3 waste audit and reporting system, improving facility safety systems, implementing a Risk-Based Inspection (RBI) program for pipeline integrity management, and integrating ESG targets into management Key Performance Indicators (KPIs).